DNA biosensor combining single-wavelength colorimetry and a digital lock-in amplifier within a smartphone. Issue 23 (25th October 2016) - Wu, Tzu-Heng; Chang, Chia-Chen; Vaillant, Julien; Bruyant, Aurélien; Lin, Chii-Wann
Abstract : Smartphone camera based gold nanoparticle colorimetry (SCB-AuNP colorimetry) has shown good potential for point-of-care applications. Abstract : Smartphone camera based gold nanoparticle colorimetry (SCB-AuNP colorimetry) has shown good potential for point-of-care applications. However, due to the use of a camera as a photo-detector, there are major limitations to this technique such as a low bit resolution (∼8 bits mainstream) and a low data acquisition rate. These issues have limited the ultimate sensitivity of smartphone based colorimetry as well as the possibility to integrate efficiently a more sensitive approach such as detection based on a lock-in amplifier (LIA). In this paper, we improve the metrological performance of the smartphone to overcome existing issues by adding the LIA capability to AuNP sensing. In this work, instead of using the camera as a photo-detector, the audio jack is used as a photo-detector reader and function generator for driving a laser diode in order to achieve a smartphone based digital lock-in amplifier AuNP colorimetric (SBLIA-AuNP colorimetry) system. A full investigation on the SBLIA design, parameters and performance is comprehensively provided. It is found that the SBLIA can reduce most of the noise and provides a detection noise-to-signal ratio down to −63 dB, which is much better than the −49 dB of the state-of-the-art SCB based method. A DNA detection experiment is demonstrated to reveal the efficacy of the proposed metrological method. The results are compared to UV-visible spectrometry, which is the gold standard for colorimetric measurement. Based on our results, the SBLIA-AuNP colorimetric system has a detection limit of 0.77 nM on short strand DNA detection, which is 5.7 times better than the 4.36 nM limit of a commercial UV-visible spectrometer. Judging from the results, we believe that the sensitive SBLIA would be further extended to other optical diagnostic tools in the near future.